Pengaruh Model Pembelajaran Kontekstual Berbantuan Media Monopoli Terhadap Hasil Belajar IPS Kelas V SD 3 Padurenan - Bayu Radya, Wisnu; Fajrie, Nur; Ardana Riswari, Lovika (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2023)
Learning carried out in class V SD 3 Padurenan, teachers still use the lecturing method (teacher centered), lack of use of learning media and low interest in learning so that it can affect student learning outcomes. In accordance with these problems, the purpose of this study is to describe the effect of monopoly media-assisted contextual learning models on social studies learning outcomes for elementary school students. The approach to this research is to use a quantitative research approach with the Pre-Experimental method. The population in this study were all fifth grade students at SD 3 Padurenan for the 2022/2023 academic year. The sample in this study used a purposive sampling technique. The sample used in this study were 15 fifth grade students. Data collection techniques in this study were tests, interviews, observation and documentation. Data analysis techniques in this study using. Data collection techniques by means of tests, observations and documentation. Analysis test can be done by t-test by measuring the normality test first. Meanwhile, in the N-gain score analysis test on social studies learning outcomes, it is known that students get results of 61, this shows the category